Islam, Inequality and Pre-Industrial Comparative Development - Stelios Michalopoulos; Alireza Naghavi; Giovanni Prarolo (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2014)
This study explores the interaction between trade and geography in shaping the Islamic economic doctrine and in turn the comparative development of the Muslim world. We build a model where an unequal distribution of land quality in presence of trade opportunities conferred differential gains from trade across regions, fostering predatory behavior from the poorly endowed ones. We show that in such an environment it was mutually beneficial to institute an economic system of income redistribution featuring direct income transfers in return for safe passage to conduct trade. A commitment problem, however, rendered a merely static redistribution system unsustainable. Islam added a set of dynamic redistributive rules that were self-enforcing under large gains from trade and high proportions of arid land. While such principles fostered the expansion of trade within the Muslim world they limited the accumulation of wealth by the commercial elite, shaping the economic trajectory of Islamic lands in the preindustrial era.
Keywords: O10; O13; O16; O17; O18; F10; Z12; 330